The Influence of Mineralogical and Petrographic Properties on the Abrasivity and Abrasiveness of Natural Stones - Mucha, Kamil; Bednarek, Łukasz; Hydzik-Wiśniewska, Joanna; Jonczy, Iwona; Nowak, Jacek (Archives of Mining Sciences, 2026)
The article discusses the relationship between mineralogical and petrographic properties and the wear resistance (abrasiveness) and abrasive characteristics (abrasivity) of natural stones. Abrasiveness is critical for the durability and functionality of these materials in construction applications. In contrast, rock abrasivity is assessed in the context of tool wear during stone processing. The research focuses on the mineralogical and petrographic characteristics of various types of natural stones, such as sandstones, granites, dolomites, and limestones, and their impact on the mechanical properties of these rocks. The article presents the results of laboratory tests that determine the degree of rock abrasivity and abrasiveness of natural stones, which is essential for selecting appropriate materials for specific construction purposes. The Böhme Abrasion Wheel Tester was used to assess rock abrasiveness, while the proprietary AGH abrasivity test was employed to evaluate rock abrasivity. The type of minerals within the stone's structure and the nature of the mineral binder directly affect the strength and abrasive properties of natural stones. The article also highlights the importance of material homogeneity and porosity in wear resistance.